El juego de los niños en transición - Gloria E. Briceño Alcaraz (Estudios sobre las Culturas Contemporáneas)
The psychological research and investigations that been conducted to date on the play of yoimg children have mostiy followed Piaget (1959). According to this theory, children´s play is a natural phenomenon accompanying the intellectual development of each child, ratlier than a much more complex phenomenon in which other important social and cultural factors are involved. This essay is part of wider research that analyzes children´s play in its natural environment from an ethnograpliical perspective. I will concentrate on gender differences encoimtered in an uiban middle class group (located in the city of Guadalajara, Mexico), as well as on how far the socio-cultural environment affects play and how certain themes, roles and creativity result, depending on this important factor.